Developing a sustainable logistics service quality scale for logistics service providers in Egypt - Ahmed Hussein Ali; Ani Melkonyan; Bernd Noche; Tim Gruchmann (Logistics, 2021)
The role of sustainability has made it a vital point to measure companies' financial performances and sustainability practices along the overall supply chain. Logistics service providers (LSPs) are among the supply chain actors that need to consider sustainability practices to present a better sustainable service. Therefore, we studied LSPs in Egypt, as Egypt has set sustainability goals in the logistics sector to be achieved by 2030. This research proposes a new sustainable logistics service quality (SLSQ) scale through reviewing the literature on sustainable service quality (SSQ) and logistics service quality (LSQ). While additional semi-structured interviews were conducted with LSP companies in Egypt to formulate the SLSQ scale for this specific region, the Q-sorting technique was used to confirm SLSQ measurements. Hence, we present a scale to evaluate Egypt's overall LSPs' service quality. Our research thereby contributes to the theory by proposing a new framework that measures the SLSQ in LSP companies in emerging countries and to the practice by tying the framework to accompany Egyptian law. The results are discussed against previous literature and concluded by showing limitations and potential future research avenues.
Keywords: 650; logistics service providers (LSPs); logistics service quality (LSQ); sustainable logistics service quality (SLSQ); sustainable service quality (SSQ); Logistikdienstleister; Dienstleistungsqualität; Nachhaltigkeit; Ägypten